Recreation use value of Wondo Genet wetland ecosystem - Ethiopia - Ali, Mohammed (SLU/Dept. of Forest Resource Management, 2007)
Wondo Genet Resort Hotel is one of the most well-known nature-based recreation sites in Ethiopia. The main attractions of the site includes: the hot spring water for bathing and swimming; the forested landscape, streams, birds and other wildlife in the surrounding; and the cafeteria, bar and bedroom services. The attractive quality of the site for many of the users is its nature-based resources. The natural ecosystem of the area can be described as wetland which can be categorized under fresh water or geothermal springs or streams and creeks category according to RAMSAR, (1971) classification of wetland types.